A Throne for Sisters (Book One) - Morgan, Rice (Lukeman Literary, 2016)
"Morgan Rice has come up with what promises to be another brilliant series, immersing us in a fantasy of valor, honor, courage, magic and faith in your destiny. Morgan has managed again to produce a strong set of characters that make us cheer for them on every page....Recommended for the permanent library of all readers that love a well-written fantasy." --Books and Movie Reviews, Roberto Mattos (regarding Rise of the Dragons) From #1 Bestseller Morgan Rice comes an unforgettable new fantasy series. In A THRONE FOR SISTERS (Book one), Sophia, 17, and her younger sister Kate, 15, are desperate to leave their horrific orphanage. Orphans, unwanted and unloved, they nonetheless dream of coming of age elsewhere, of finding a better life, even if that means living on the streets of the brutal city of Ashton. Sophia and Kate, also best friends, have each other's backs-and yet they want different things from life. Sophia, a romantic, more elegant, dreams of entering court and finding a noble to fall in love with. Kate, a fighter, dreams of mastering the sword, of battling dragons, and becoming a warrior. They are both united, though, by their secret, paranormal power to read other's minds, their only saving grace in a world that seems bent to destroy them. As they each embark on a quest and adventure their own ways, they struggle to survive. Faced with choices neither can imagine, their choices may propel them to the highest power-or plunge them to the lowest depths. A THRONE FOR SISTERS is the first book in a dazzling new fantasy series rife with love, heartbreak, tragedy, action, magic, sorcery, fate and heart-pounding suspense. A page turner, it is filled with characters that will make you fall in love, and a world you will never forget. Book #2-A COURT FOR THIEVES-will be released soon. "An action packed fantasy sure to please fans of Morgan Rice's previous novels, along with fans of works such as The Inheritance Cycle by Christopher Paolini.... Fans of Young Adult Fiction will devour this latest work by Rice and beg for more." --The Wanderer, A Literary Journal (regarding Rise of the Dragons)
Keywords: Young Adult, New Adult